Motivation of staff and the heads of municipal administration - Sterev, Nikolay; Blagoev, Dimitar; Kopeva, Diana (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Success in the work of the public administration is a result of the quality of human resources. Increasing efficiency in the management of human resources is based on motivation, and it is an important part of ensuring sustainable development of the municipality and its administration. The paper explores and analyzes the motivation of the staff and managers of municipal administration. It is structured in three parts: theoretical and methodological foundations of motivation, motivation profile and competences; analysis of results of a survey among employees of the municipal administration; summary and conclusions
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 476, s. 18-29
Keywords: motivation; motivational and competency profile; municipal administration; motywacja; profil motywacyjny i kompetencyjny; administracja miejska